Answer:
Congruent, SSS
Step-by-step explanation:
The dashes on the sides of the triangles represent that the corresponding lengths of the triangles are equal in length. Since it is given that all corresponding lengths of the triangles are equivalent, the triangles are congruent by the SSS (side, side, side) test.
Hope this helps :)
The equation of the line is y=6x+37
Step-by-step explanation:
You can write the equation using the slope intercept form techniques which is y=mx+c where m is the slope of the line and cis they intercept constant.
Given the point (-6,1) and slope m=6then
Δy/Δx =m
![y-1/x--6 = 6\\\\y-1/x+6=6\\\\\\y-1=6(x+6)\\\\\\y-1=6x+36\\\\\\y=6x+36+1\\\\y=6x+37](https://tex.z-dn.net/?f=y-1%2Fx--6%20%3D%206%5C%5C%5C%5Cy-1%2Fx%2B6%3D6%5C%5C%5C%5C%5C%5Cy-1%3D6%28x%2B6%29%5C%5C%5C%5C%5C%5Cy-1%3D6x%2B36%5C%5C%5C%5C%5C%5Cy%3D6x%2B36%2B1%5C%5C%5C%5Cy%3D6x%2B37)
Answer:
Column A Column B
1. x² + 6x + 8 x-3,x+2
2. x³ - 7x + 6 x+1, x+2, x+3
3. x³ - 2x² - 5x + 6 x-1, x+2, x-3
Step-by-step explanation:
Column A Column B
1. x² + 6x + 8 x-3,x+2
2. x³ - 7x + 6 x+1, x+2, x+3
3. x³ - 2x² - 5x + 6 x-1, x+2, x-3
Using Factor theorem we put values of x = ±1,±2,±3 in each of the polynomials unless we get a zero.
1. x² + 6x + 8
= 1+6(1) +8= 15
1. x² + 6x + 8
4+ 12+8 = 24
1. x² + 6x + 8
(-1)² + 6(-1)+ 8
= 1-6+8= 3
1. x² + 6x + 8
(-2)² + 6(-2)+ 8
= 4-12+8= 0
1. x² + 6x + 8
(3)²+ 6(3) +8
= 9+18+8 ≠ 0
1. x² + 6x + 8
(-3)²+ 6(-3) +8
= 9-18+8 =-1
For this polynomial we have x+2= 0 or x=-2, x-3= 0 , x=3
2. x³ - 7x + 6
1-7+6= 0
2. x³ - 7x + 6
(-1)³-7(-1) +6
= 13-1≠0
2. x³ - 7x + 6
(2)³-7(2) +6
= 8-14+6= 0
2. x³ - 7x + 6
(-2)³-7(-2) +6
= -8 +14+6
2. x³ - 7x + 6
(-3)³-7(-3) +6
= -27+21+6 = 0
For this polynomial we have x+1= 0 , x+2 = 0 and x+3= 0, or x=-1,-2,-3
3. x³ - 2x² - 5x + 6
(1)³-2(1)²-5(1)+6
= 0
3. x³ - 2x² - 5x + 6
(-1)³-2(-1)²-5(-1)+6
= -1 -2 +5+6
=8
3. x³ - 2x² - 5x + 6
(2)³-2(2)²-5(2)+6
= 8-8-10+6
=-4
3. x³ - 2x² - 5x + 6
(-2)³-2(-2)²-5(-2)+6
= -8-8+10+6
=0
3. x³ - 2x² - 5x + 6
(3)³-2(3)²-5(3)+6
= 27-18-15+6
=0
3. x³ - 2x² - 5x + 6
(-3)³-2(-3)²-5(-3)+6
= -27-18+15+6
=-14
For this polynomial we have x-1= 0 ,x+2=0, x-3= 0or x=1,-2,3
Answer:
Step-by-step explanation:
Required man days to complete the job = 8 * 6
= 48 Man Days
Required labors to complete the job by 15 days = 48/15
= 3.2
It means, it is required 4 labors can complete the certain work by 15 days
Answer:
ik
Step-by-step explanation:
i think it is 120 is that the answer